A CORPUS-BASED ANALYSIS OF LEXICAL FREQUENCY AS EVIDENCE IN UNDERGRADUATE LITERARY ARGUMENTATION - Agnes Widyaningrum (Linguists : Journal of Linguistics and Language Teaching, 2026)
Despite the growing use of corpus tools in literary studies, little is known about how undergraduate writers transform corpus-generated lexical frequency into argumentative evidence. This study investigates how lexical frequency outputs from Voyant Tools are used as evidential support in undergraduate literary argumentation. Using a qualitative discourse-analytic approach, the study examines three purposively selected student mini-research articles from a corpus-assisted literature course. The analysis identifies a recurring frequency-to-claim trajectory in which writers select a salient lexical item, report its frequency, connect the numerical observation to an evidential bridge, and extend it into a literary interpretation. Across the dataset, lexical frequency functions as a warrant for keyword selection, thematic centrality, theoretical labeling, and methodological legitimacy. At the same time, the findings show that frequency alone does not ensure interpretive validity; persuasive literary argumentation depends on contextual triangulation, particularly through keyword-in-context (KWIC) analysis. As a small-scale exploratory study, this article proposes the frequency-to-claim trajectory as a conceptual model for understanding how quantitative outputs are transformed into qualitative literary reasoning and highlights its pedagogical implications for corpus literacy and undergraduate literary writing.